First geoarchaeological study of a Palaeolithic site on the northern edge of the Iranian Central Desert: Mirak (Semnan, Iran). (June 2022) - Akhavan Kharazian, Mohammad; Jamet, Guillaume; Puaud, Simon; Vahdati Nasab, Hamed; Hashemi, Milad; Guerin, Guillaume; Heydari, Maryam; Antoine, Pierre; Bahain, Jean-Jacques; Berillon, Gilles
Abstract: Mirak is a Palaeolithic site in Iran comprising several localities ("mounds") scattered over a dry floodplain environment extending from the southern foothills of the Alborz Mountains to the northern edge of the Central Desert in the Semnan area. The area has been studied since 2015 by an Iranian-French archaeological mission. The archaeological excavations carried out at the Mirak N°8 mound uncovered a 7 m-thick pedo-sedimentary sequence, in which two sequences corresponding to contrasting depositional environments have been observed. Sequence I, comprising alternating horizons of poorly pedogenised clayey silt intercalated with sand layers, is interpreted as an alluvial pedo-sedimentary body deposited in a wetland (floodplain) environment during cold periods, periodically interrupted by shallow sheet flooding deposits. According to the stratigraphy, OSL dates and sedimentological analyses, there is a long sedimentary hiatus before the occurrence of sequence II which corresponds to calcareous aeolian deposits typical of a desert environment. The Mirak N°8 deposits were affected by several stages of incipient aridisol formation with desiccation cracks implying a gradually increasing prevalence of more arid conditions. According to the OSL data, the Mirak N°8 sequence was deposited from the Late Pleistocene to the Late Holocene (52ka to 0.4ka). In this sequence, upper Palaeolithic remains were recovered at distinct levels and it can be presumed that the most recent archaeological layer is made up of palimpsests resulting from repeated human occupations. Results from various mineralogical and sedimentological analyses (XRD, FTIR, SEM, optical microscopy) show very minor differences in mineralogy throughout the record regardless of the type of depositional regime, suggesting a local, and most probably polygenic, sedimentary source. Both alluvial and aeolian accumulations were subjected after deposition to a variety of post-sedimentary pedogenesis processes indicated by pedogenic features characteristic of calcareous, gypsiferous aridisols (Bk, By), including ferruginous root coatings, evaporates and little-developed pedo-structures and horizons. Apparent differences in colour between the two sequences at Mirak N°8 can be attributed to deposition in environments with varying iron contents and oxygenizing conditions, presumably related to higher groundwater levels and Fe-reducing conditions, especially for the units deposited during the late Pleistocene as opposed to the generally warm and dry conditions of the Holocene.